Lone mothers' time allocations: choices and satisfactions. Issue 1 (March 2013) - Le, Anh T.; Miller, Paul W.
Abstract : This paper uses the 2006 Australian Time Use Survey to examine the allocation of time to personal care, employment‐related activities, home duties, leisure and child care of lone mothers, in comparison to the time allocations of single women, women in childless couples and partnered mothers. Both primary and secondary time allocations are considered. The satisfactions that women report concerning their current time allocations are also analysed. The time use and satisfaction data are described using both tabulations and multiple regression methods. Lone mothers are shown to have similar time allocations as the other types of households, even though they have different financial and time resources. This raises the concern that lone mothers' desire or need to maintain such time allocations may lead to task overload. Consistent with this, lone mothers are found to be less satisfied with the way they allocate their time than single women and partnered mothers. The tensions associated with time use among lone mothers discussed in the literature are real, and important.